Vitamin D deficiency and risk of cardiovascular diseases: a narrative review - Babikir Kheiri; Ahmed Abdalla; Mohammed Osman; Sahar Ahmed; Mustafa Hassan; Ghassan Bachuwa (BMC, 2018)
Abstract Vitamin D, a fat-soluble prohormone, has wide-ranging roles in the regulation of many physiological processes through their interactions with the vitamin D receptors (VDR). It plays a major role in bones and calcium metabolism. Vitamin D deficiency is not uncommon and it has been associated with many health-related issues, including skeletal and non-skeletal complications. The association of low vitamin D and cardiovascular diseases and risk factors has been explored in both animal and human studies. However, studies and trials on the effect of vitamin D supplementation on cardiovascular risk factors and hypertension are conflicting with inconsistent results. Therefore, large, well-powered randomized controlled trials are warranted. If successful, supplementation with easy and low-cost vitamin D can impact our health positively. Here, we summarized the evidence for the association of vitamin D, cardiovascular diseases and risk factors, including coronary artery diseases, stroke, and hypertension, and mortality, with special consideration to resistant hypertension.